Contemporary guidelines on diagnosis of urticaria - Czarnecka-Operacz, Magdalena (Dermatology Review/Przegląd Dermatologiczny, 2011)
Urticaria is a frequent dermatose of complex and diverse etiology. Generally it is easy to diagnose but identification of elicitating factors still presents a great challenge for physicians. Each patient requires an individually tailored panel of diagnostic procedures including basic ones as well as specific provocations, which need to be selected according to the clinical characteristic of the case. Provocation tests require hospitalization because serious systemic side effects may be induced during the diagnostic procedure and anaestesiologic intervention may be necessary. Acute type of urticaria is usually allergic in origin and diagnostic approach is not as complex as in the case of chronic type of the disease. Recently published guideline on definition, classification and diagnosis of urticaria is a very useful document containing selection of rules and advices which should be implemented in the daily practice of dermatologists, allergologists, paediatritians as well as general practitioners.